Performance Analysis and Actual Needs Figures for Operation and Maintenance at D.I.R. Sebakung - Julianto, Jimmy; Nur, Alpian; Sundari, Yayuk Sri (PT ARRUS Intelektual Indonesia, 2025)
East Kalimantan has great potential as a food production center in Indonesia, supported by the Sebakung Swamp Irrigation Area (DIR) which covers an area of ​​13,500 hectares with a functional area of ​​10,290 hectares. However, inefficient irrigation management and inadequate infrastructure maintenance have resulted in suboptimal land use and decreased agricultural productivity. This study aims to analyze the performance of the existing irrigation network and determine the budget required for its operation and maintenance. The study was conducted using field observations and regulatory guidelines, including Ministerial Regulation No. 12/PRT/M/2015 and No. 23/PRT/M/2017. The results of the study indicate that most irrigation channels are below Index 3, indicating significant sedimentation and vegetation growth that inhibits water flow. The overall channel condition index is 2.10 with a network functional level of 72.50%, while several water gates in certain villages are severely damaged with an Index classification of 4. The total operational cost of managing the irrigation network is IDR 292,300,000.00 which includes personnel incentives, monitoring, office operations, and equipment maintenance. Routine and periodic maintenance costs vary, with the highest budget allocated to Sri Raharja and Babulu Laut, totaling more than IDR 187,200,000.00. To improve irrigation performance, systematic management strategies such as routine dredging, vegetation control, and rehabilitation of priority infrastructure must be implemented. These efforts will improve irrigation efficiency, ensure optimal water distribution, and support agricultural productivity in East Kalimantan.